PENERAPAN STRATEGI CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA INTENSIF SISWA PADA MATA PELAJARAN BAHASA INDONESIA - Nova Ainaya Alfaticha; Fita Mustafida; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Improving intensive reading skills by applying the CIRC strategy to Indonesian class V students of SD Negeri Gunungsari. This research was conducted with the aim of improving students' intensive reading skills by applying the Cooperative Integrated Reading and Composition (CIRC) strategy. The type in this research is Classroom Action Research (CAR), the subjects in this study are teachers and students of class V SD Negeri totaling 35 students. Data collection techniques in this study are interviews, observations, tests, and documentation. The data analysis technique in this study used descriptive qualitative and quantitative data. The results of this study indicate an increase in students' intensive reading skills in Indonesian subjects. This is evidenced from the learning outcomes in the pre-cycle to cycle II. As for the results in cycle 1 of 35 students, students who succeeded in achieving the KKM (75) were 12 students or (34.29%), in the first cycle as many as 21 students (60%), in the second cycle as many as 30 students (88.57 %). It can be concluded from the results of this study that by implementing the CIRC strategy, it can increase the intensive reading skills of the fifth grade students of the Indonesian language subject at SD Negeri Gunungsari.